Effects of p-chlorophenylalanine (pcpa) on ethanol withdrawal syndrome in rats - Uzbay, İ. Tayfun and Kayır, Hakan (Journal of Dependence, 2007)
Objective: In the present study, the effects of p-chlorophenylalanine (pCPA), a serotonin depleting agent, treatment on ethanol withdrawal syndrome have been investigated in rats. Thus, contributions of central serotonergic system to various signs of ethanol withdrawal syndrome have been examined and clarified. Methods: Ethanol (7.2% v/v) was given to adult male Wistar rats by a liquid diet for 21 days. pCPA (100 mg/kg) and saline were injected to rats intraperitoneally 24 h before ethanol withdrawal testing. After 2nd, 4th and 6th h of ethanol withdrawal, rats were observed for 5 min, and withdrawal signs, including locomotor hyperactivity, agitation, stereotyped behavior, wet dog shakes, tremor and audiogenic seizures were recorded or rated. pCPA (100 mg/kg) were also administered to no ethanol-dependent control rats and locomotor activity was measured and evaluated like in ethanol-dependent group. Results: pCPA treatment produced some significant increases in locomotor activity of both control and ethanoldependent rats during the observation period. pCPA caused some increases the severity of agitation and intensity of wet dog shakes at 2nd and 6th hrs of ethanol withdrawal, respectively. It was no effective on the other signs of ethanol withdrawal except audiogenic seizures. pCPA pretreatment inhibited significantly the incidence of audiogenic seizures. Conclusion: Our findings suggest that pCPA intensified locomotor hyperactivity, agitation and wet dog shakes but attenuated audiogenic seizures during ethanol withdrawal in ethanol-dependent rats. These signs of ethanol withdrawal may be related to serotonergic mechanisms in central nervous system.